Singularities of the planar green function in the spectral domain - LAPRUS, W.; DANICKI, E. (Archives of Acoustics, 1997)
The surface acoustic wave amplitudes at the boundary of a piezoelectric half-space satisfy a matrix relation which is characteristic of the medium. The elements of the matrix are functions of slowness. In the paper, the singularities of the matrix are investigated at cutoff points of bulk waves. An approximated formula is derived for the matrix in the neighborhood of the greatest cutoff point, which also takes into account the singularity related to the Rayleigh wave. The results of numerical calculations are presented for several piezoelectrics.